Moderasi Beragama: Wujudkan Harmonisasi Antar Umat Beragama - Munir Munir; Farida Isroani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Islam is a teaching that reliably shows the meaning of harmony and harmony. The Qur’an is also believed to include this word as al-Salam (a term for Allah the Most Calm), muslim (a person who seeks a peaceful life), silm (harmony itself), Islam (a term for the religion sent by the Prophets). Off lifting Allah’s expression), so that humans live in harmony with themselves, their families, social networks, the grave, until they enter heaven “dār al-salam”. The word welcoming comes from Arabic which means harmony, peace and is used mainly as an explanation of respect. It conveys the meaning of a sense of security, but contains the essence of being free from all dependence and tension, so that life feels calm, serene and safe. Greetings are one of the opening expressions in communication. How can communication run smoothly, let alone build harmony between religious communities, if greetings as a means of greeting non-Muslims are prohibited? The East Java MUI’s appeal, which was addressed specifically to officials not to say interfaith greetings at official events, has become controversial and polemic. In many circles. From cyberspace to the real world, this issue is widely discussed. Apart from the many parties who are against this appeal, there are also quite a few parties who are pro.